METHODOLOGICAL FEATURES OF STUDYING THE BASICS OF FINANCIAL LITERACY IN THE 8TH GRADE MATHEMATICS COURSE OF NUS: МЕТОДИЧНІ ОСОБЛИВОСТІ ВИВЧЕННЯ ОСНОВ ФІНАНСОВОЇ ГРАМОТНОСТІ В КУРСІ МАТЕМАТИКИ 8 КЛАСУ НУШ - Shkolnyi, Oleksandr (Physical and Mathematical Education, 2025)
Formulation of the problem. In modern conditions, an important aspect of the development of students' personality is their awareness in the field of financial calculations. In addition, “entrepreneurship and financial literacy” is one of the 11 key competencies, the formation of which is provided for by current state documents regulating educational activities in Ukraine, in particular, the concept of implementing the New Ukrainian School (NUS) reform. Analysis of sources on the introduction of the basics of financial literacy into the educational process showed that it is currently only at the initial stage and has significant national characteristics, compared with analogues in other countries of the world.The purpose of the article is a detailed presentation of the methodological features of studying the basics of financial literacy of 8th grade NUS students in mathematics lessons in order to properly form the corresponding key competency provided for by the State Standard of Basic Secondary Education, using the author's educational materials.Materials and methods. Theoretical analysis of methodological literature, comparative analysis, systematization, and generalization of existing theoretical research on the topic of the article were employed, as well as pedagogical observation and generalization of one's own pedagogical experience in teaching mathematics to 8th-grade students at the National Secondary School.Results. According to the model educational program and textbooks, one of the authors of which is the author of this article, the section “Fundamentals of Financial Literacy”, which combines the material of the two paragraphs “Formulas of Simple and Compound Interest and Discounts and Their Application” and “Dated Amounts. Equivalent Amounts at a Given Interest Rate” is introduced into the mathematics course for the 8th grade of the National Secondary School. This material is largely new to Ukrainian mathematics teachers; therefore, both the theoretical content itself and its methodological features should be carefully explained. Such an explanation is implemented in the textbook itself, in the teacher's book, as well as in additional interactive materials (educational videos) created by the author team of the educational program and the textbook. The article offers methodological comments on the most challenging theoretical material for students to understand, as well as methodological advice on organizing the study of this material.Conclusions. As shown by the survey of students during the probation of the textbook and the survey of mathematics teachers who conducted this probation, the presented approaches to teaching students the basics of financial literacy are well received by adolescents. The results of control measures also show that this material is accessible and understandable for the majority of students who studied it. Also, all the surveyed teachers themselves understood the relevant theoretical material well, and as a result of proper cooperation with the author's team of the textbook and with the help of a book for teachers, this process did not cause them significant difficulties. We believe that the author's educational materials demonstrate the effectiveness of the methodological approaches to studying the basics of financial literacy described in the article, which will ensure the proper development of the relevant key competence in students, as stipulated in the State Standard of Basic Secondary Education.
Keywords: New Ukrainian School; State Standard of Basic Secondary Education; model mathematics program; mathematics textbook; key competencies; entrepreneurship and financial literacy